Trust, computing, and society - Harper, Richard H. R. (Cambridge : Cambridge University Press, 2014)
The internet has altered how people engage with each other in myriad ways, including offering opportunities for people to act distrustfully. This fascinating set of essays explores the question of trust in computing from technical, socio-philosophical, and design perspectives. Why has the identity of the human user been taken for granted in the design of the internet? What difficulties ensue when it is understood that security systems can never be perfect? What role does trust have in society in general? How is trust to be understood when trying to describe activities as part of a user requirement program? What questions of trust arise in a time when data analytics are meant to offer new insights into user behavior and when users are confronted with different sorts of digital entities? These questions and their answers are of paramount interest to computer scientists, sociologists, philosophers and designers confronting the problem of trust.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Trust; Computer security